Factores asociados y proporción de la población con anticuerpos contra Yersinia pestis, provincia de Ascope, La Libertad, 2011 - Garcia Vara, Patricia (2019)
Plague in a disease of great importance in Public Health and global distribution, a very old disease causing three major pandemics of human plague worldwide with millions of human deaths. A cross-sectional observational study was carried out, in which the associated factors and proportion of the population with antibodies against Yersinia pestis, province of Ascope, department of La Libertad, were determined in 2011. In this study, 144 inhabitants of the province of Ascope of the department of La Libertad, which were interviewed and proceeded with the collection of data and samples required for the study, the samples were tested ELISA IgG to determine the proportion of Yersinia pestis. The average age of the inhabitants was 41 years, with 55.56% from 15 to 44 years old, the sex that predominated was female with 70.83%, the education of the inhabitants with full secondary education followed by primary school complete with 49.31% and 39.58 % respectively. The detection of IgG antibodies against Yersinia pestis by means of the ELISA test was 52.78%, in which no differences were found in the presence of IgG antibodies against Yersinia pestis according to sex, in relation to age. IgG antibodies against Yersinia pestis between the ages of 15 to 44, being statistically significant (p <0.001), with increased risk according to the increase in age. With respect to the risk factors associated with the presence of IgG antibodies against Yersinia pestis, it was observed an association of having one type of floor material (OR = 0.27, p = 0.025), raising cats in their homes (OR = 0.31, p = 0.032) and the presence of rats in their homes (OR = 3.34, p = 0.015). It was determined that the risk factors associated with Yersinia pestis infection by the IgG ELISA test were age and rats. As well as the protective effect factor was the breeding of cats. The present study will broaden the knowledge about this disease caused by Yersinia pestis in Perú.